At men dan toch echt uit kalebassen? Proto-Bantoe en de domesticatie van Cucurbitacreae. - Bulckens, Annelies (Afrika Focus, 1998)
This paper examines the history of calabashes in the Bantu-world. Due to con- servation problems of floral remains in tropical areas, no material traces of these fruits have been excavated untill now. The historical linguistic approach adopted in this paper, gives an overview of the evolution and history of different words signifying calabash and allows the formulation of some conclusions on agricultural history. KEY WORDS : comparative linguistics, Bantu, calabash, Curubits